2013
DOI: 10.1002/ggge.20044
|View full text |Cite
|
Sign up to set email alerts
|

Slow slip and tremor search at Kilauea Volcano, Hawaii

Abstract: Kilauea Volcano, Hawaii, has hosted a long series of slow slip events observed since the installation of the continuous GPS network in 1996. Kilauea's slow slip events are inferred to occur on the decollement fault at 8 km depth beneath its south flank, with a location updip of the epicenters of large, regular earthquakes. Fault slip typically lasts about two days, and the events have magnitudes equivalent to Mw 5.3–6.0. While slow slip events in subduction zones are commonly accompanied by tectonic tremor (al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 92 publications
(157 reference statements)
0
16
0
Order By: Relevance
“…In Mexico, Liu et al [] noted increases in seismicity during slow slip events (SSEs) in 1998, 2001–2002 and 2006. At the Kilauea volcano, seismic swarms have systematically occurred during slow slip marking the destabilization of the southeast flank of the volcano [ Montgomery‐Brown et al , , , ]. The rapid anomalous increase of earthquake rate can therefore reveal slow deformation transients associated with slow aseismic slip, as long as these transients occur in seismicity‐prone areas, and at shallow depth [ Delahaye et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…In Mexico, Liu et al [] noted increases in seismicity during slow slip events (SSEs) in 1998, 2001–2002 and 2006. At the Kilauea volcano, seismic swarms have systematically occurred during slow slip marking the destabilization of the southeast flank of the volcano [ Montgomery‐Brown et al , , , ]. The rapid anomalous increase of earthquake rate can therefore reveal slow deformation transients associated with slow aseismic slip, as long as these transients occur in seismicity‐prone areas, and at shallow depth [ Delahaye et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent geodetic observations have revealed that slow slip events (SSEs), which are episodic fault movements that are so slow that they do not radiate large amplitude seismic waves, occur worldwide [e.g., Hirose et al , ; Dragert et al , ; Lowry et al , ; Cervelli et al , ; Ozawa et al , ; Douglas et al , ; Ohta et al , ; Outerbridge et al , ]. SSEs exhibit considerable variability in their basic features, including duration, magnitude, slip propagation velocity, and depth [e.g., Schwartz and Rokosky , ; Peng and Gomberg , ; Gao et al , ; Montgomery‐Brown et al , ]. In addition, a number of SSEs are found to accompany other “slow earthquakes,” such as low‐frequency tremors [ Rogers and Dragert , ; Obara et al , ] and very low frequency earthquakes [ Ito et al , ; Hirose et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike many SSEs previously observed at plate boundary subduction zones, such as southwestern Japan [Hirose et al, 1999], Cascadia on the western coast of the USA and Canada [Dragert et al, 2004], and Guerrero in southern Mexico [Larson et al, 2004], Montgomery-Brown et al [2013] reported that no associated tectonic tremor was detected during Kīlauea's SSEs, suggesting that these SSEs reflect somewhat distinct slip processes compared to those at plate boundary subduction zones.…”
Section: The Slow Slip Events At Kīlauea Hawaiimentioning
confidence: 67%
“…Brooks et al [2006] Brooks et al [2008] noted that a dike intrusion occurred a few hours before the 2007 slow slip event, suggesting that the intrusion triggered the 2007 SSE. The most recent 2010 and 2012 SSEs [Poland et al, 2010;Montgomery-Brown et al, 2013] are larger than the previous large events in 1998, 2000, 2005, and 2007. However, no corresponding dike intrusion was associated with either of the other events.…”
Section: The Slow Slip Events At Kīlauea Hawaiimentioning
confidence: 96%